PENGARUH KOMPENSASI FINANSIAL, LINGKUNGAN KERJA NON FISIK, DAN KOMITMEN ORGANISASIONAL TERHADAP SEMANGAT KERJA KARYAWAN - Darmawan, I Gede Widya; Wibawa, I Made Artha (E-Jurnal Manajemen, 2019)
The purpose of this study was to study comparative financial research, non-physical work environment, and organizational commitment to morale. This research was conducted at KSP. Tat Twam Asi Denpasar, the number of samples taken was 30 employees, with the method of saturated samples / census. Data collection is done through interviews and questionnaires. The analysis technique uses multiple linear regression analysis techniques. At the initial observation found in KSP. Tat Twam Asi Denpasar has a problem related to the employee morale. This can be seen from the high employee absentee level. Based on the results of the analysis found that financial compensation, non-physical work environment, and organizational commitment simultaneously or partially positive commitment to employee morale. This shows that the higher compensation and organizational commitment, the higher employee morale will be. KSP. Tat Twam, the approved company considers the average value indicators that are approved by the average value variable. Keywords: financial compensation, non physical work environment, commitment organizational, employee morale.